2013
DOI: 10.5402/2013/217505
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Efficacy of Fiberoptic Bronchoscopy in the ICU: Have They Changed Since Its Introduction in Clinical Practice?

Abstract: is properly cited.Purpose. We describe characteristics, utility, and safety of fiberoptic bronchoscopy (FOB) in an intensive care unit (ICU). Methods. Prospective and descriptive cohort of patients admitted to a respiratory ICU from March 2010 to June 2012. Results. A total of 102 FOBs were performed in 84 patients among 580 patients that were admitted to the ICU. Mean age was 48 ± 17 years. FOB was useful in 65% of diagnostic procedures and 83% of therapeutic procedures, with an overall utility of 75%. Indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The spectrum of BAL fluid microbial isolates obtained from patients admitted to ICU varies across studies. In our study, Acinetobacter baumanii was the commonest bacterial isolate found, and similar results were obtained from studies conducted in ICU settings in Brazil, Mexico, India, and Iran, where one-third or more of the isolates were of Acinetobacter baumanii [ 3 , 8 , 16 18 ]. Contrary to this in a study from an Egyptian teaching hospital, the commonest isolate in the ICU setting was Pseudomonas aeruginosa , followed by Acinetobacter [ 2 ].…”
Section: Discussionsupporting
confidence: 89%
“…The spectrum of BAL fluid microbial isolates obtained from patients admitted to ICU varies across studies. In our study, Acinetobacter baumanii was the commonest bacterial isolate found, and similar results were obtained from studies conducted in ICU settings in Brazil, Mexico, India, and Iran, where one-third or more of the isolates were of Acinetobacter baumanii [ 3 , 8 , 16 18 ]. Contrary to this in a study from an Egyptian teaching hospital, the commonest isolate in the ICU setting was Pseudomonas aeruginosa , followed by Acinetobacter [ 2 ].…”
Section: Discussionsupporting
confidence: 89%
“…Sixty-seven percent of the bronchoscopies were requested to improve ventilation through bronchial plug removal. This is much more common than that observed with ICU non-COVID patients-about 25% 5 and could be explained by technical ventilation adaptations related to the pandemic. Usually, during invasive ventilation, warming and moistening of inhaled gases is obtained by the addition of heated humidifiers (HH) or heat-moisture exchangers (HME).…”
mentioning
confidence: 81%
“…In the study by Alvarez-Maldonado et al . that included 102 critical care patients, 65% of the patients are reported to have developed transient hypoxemia during bronchoscopy, while 3.5% developed other minor complications such as bleeding or dysrhythmia ( 19 ). Prebil et al .…”
Section: Discussionmentioning
confidence: 99%